Family Counseling Da'wah Model at The Ta'lim An-Nur Council in Serang City; Contextualization of Fiqh Munaqahat - Aufa, Maya (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Psychic problems have become a topic of discussion in the life of heterogeneous communities, so this fact is a challenge for preachers not to be preoccupied with syi'ar activities that focus on activities on the pulpit in a linear pattern. Non-formal educational institutions such as the Taklim Council have their own curriculum, held regularly and regularly, their existence is used as a place for religious deepening and counseling facilities for those who have little leisure time due to routine as formal and non-formal workers. This empowerment activity aims to find other aspects of the taklim assembly in a housing complex in Serang, Banten, which is not limited to a place to learn religious knowledge. By using the method of empowerment of Da'wah Bil Oral with an Islamic counseling approach with the study of fiqh munaqahat. The model of Da'wah bil lisan, an approach to Islamic counseling through the study of fiqh munakahat at the Ta'lim An-Nur Council in Serang City, is effective and contributes to the household problems of the An-Nur taklim council. Da'wah which is more oriented towards wisdom, maudizoh hasanah and mujlà billati hiya ahsan is liked by pilgrims because it contributes to fundamental problems and can be used as a medium for family counseling. Islamic counseling in the study of fiqh munaqahat becomes a counselor room by the ustadzah with the fiqh munaqahat approach, can clarify the boundaries in the relationship between husband and wife related to rights and obligations.